AN AUDIT OF VANCOMYCIN PLASMA CONCENTRATIONS WHEN VANCOMYCIN IS ADMINISTERED BY CONTINUOUS INTRAVENOUS INFUSION IN NEONATES. Issue 9 (17th August 2016) - Whitticase, Louise; Holder, Gemma; Cawsey, Matt; Bedford-Russell, Alison
Abstract : Aim: To compare continuous intravenous infusions of vancomycin in achieving desired therapeutic plasma concentrations against an intermittent bolus regimen. Method: Data were collected for all babies who received a continuous infusion of vancomycin on our Neonatal Intensive Care Unit (NICU) between October 2014 and March 2015. The regimen is based on that of another hospital (Hospital A) and comprised of a loading dose of 15 mg/kg over 1 hour followed by a continuous infusion of 20–50 mg/kg/day according to creatinine and corrected gestational age (CGA). The desired therapeutic range is 15–25 mg/L. The data recorded were date and time vancomycin was commenced, corrected gestational age (CGA), day of life and creatinine level at commencement, and the dose administered in mg/kg/day. Plasma concentrations were recorded as first, second or subsequent. Babies who switched from intermittent regimen were excluded. Results were analysed according to plasma concentration i.e. first, second or subsequent and stratified by CGA, day of life and creatinine level. All concentrations were obtained retrospectively for the period January to July 2014 when vancomycin was administered by intermittent bolus regimen to allow comparison of effectiveness. The doses of vancomycin were prepared at ward level by trained neonatal nurses as there is no aseptic facility onsite. We also compared our findings with those of another hospital from 2012. Results: 49 babies received continuous vancomycin infusions and 115 plasma concentrations were analysed. Overall 62% of concentrations were within desired therapeutic range. This comprised 60.8% of first concentration, 60% of second concentration and 65.6% of subsequent concentrations. In relation to gestational age, 55.9% of concentrations for those 23–28+6 weeks CGA, 59.4% of concentrations for those 29–34+6 weeks CGA and 70.2% of concentrations for those >35 weeks CGA were in the therapeutic range. 84.6% of concentrations for those 0–6 days old, 58% of concentrations for those 7–28 days old and 60% of concentrations for those >29 days old were in therapeutic range. 62% of concentrations for those with a Cr<50 micromol/L, 69% of concentrations for those with a Cr50–70 micromol/L and 50% of concentrations for those with a Cr>70 micromol/L were in the desired therapeutic range. Adjusting the data to allow for 10% variability in the target range achieved 71.3% of all concentrations in desired therapeutic range (13.5–27.5 mg/L). Compared to the plasma concentrations obtained on intermittent bolus regimen the percentage of concentrations in the desired therapeutic range has increased from 28% to 62%. Compared to the other hospital's data, the percentage of concentrations in the desired therapeutic range is lower at 62% compared to their 77%. Conclusion: Continuous infusions of vancomycin are more effective than intermittent bolus dosing in achieving desired therapeutic concentrations. Stratification of results has not shown any appreciable difference between the groups receiving vancomycin. However, extrapolation of our findings to those from other work, where prefilled syringes prepared in pharmacy are used is limited. It is known that there is significant variability from the desired target concentration of syringes prepared at ward level. There is a need to look at procuring prefilled vancomycin syringes and undertaking a re-audit.